2018
DOI: 10.1017/ice.2017.308
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Negative Methicillin-Resistant Staphylococcus aureus Nasal Surveillance Swabs in Predicting the Need for Empiric Vancomycin Therapy in Intensive Care Unit Patients

Abstract: OBJECTIVES The role of methicillin-resistant Staphylococcus aureus (MRSA) nasal surveillance swabs (nasal swabs) in guiding decisions about prescribing vancomycin is unclear. We aimed to determine the likelihood that patients with negative MRSA nasal swabs develop subsequent MRSA infections; to assess avoidable vancomycin days for patients with negative nasal swabs; and to identify risk factors for having a negative nasal swab and developing a MRSA infection during the intensive care unit (ICU) stay. METHODS T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Nasal colonization with MRSA has been shown to be a risk factor for developing a clinical MRSA infection . In two large studies, a negative MRSA nasal swab has been shown to have a negative predictive value (NPV) greater than 99% for the development of future MRSA infections . Dangerfield B, et al analyzed 435 patients’ MRSA nasal swabs and the development of pneumonia.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Nasal colonization with MRSA has been shown to be a risk factor for developing a clinical MRSA infection . In two large studies, a negative MRSA nasal swab has been shown to have a negative predictive value (NPV) greater than 99% for the development of future MRSA infections . Dangerfield B, et al analyzed 435 patients’ MRSA nasal swabs and the development of pneumonia.…”
Section: Discussionmentioning
confidence: 62%
“…Chotiprasitsakul D, et al analyzed 12 215 patients’ MRSA nasal swabs in the ICU and demonstrated a NPV of 99.4% for MRSA infection at any timepoint. Only 0.22% of the patients who had a negative MRSA nasal swab developed a MRSA infection . In this study, the negative MRSA nasal swab resulted in potentially 7364 days of avoidable vancomycin use .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 11,441 patients with negative surveillance screening during ICU admission, only 25 patients (0.22%) developed a clinically significant MRSA infection requiring treatment resulting in an NPV of 99.4% (95% confidence interval [CI] 99.1–99.6). The investigators estimated that 7364 days of vancomycin therapy could have been avoided if vancomycin had been discontinued in the patients with negative swab results . This study excluded patients with a history of MRSA from surveillance cultures or clinical cultures within the previous 12 months .…”
Section: Evidence By Infection Typementioning
confidence: 99%
“…25 A recently published retrospective cohort study of 11,882 patients across six intensive care units (ICUs) in a 19-month period investigated the utility of the MRSA nasal swab to predict any MRSA infection. 26 In the 11,441 patients with negative surveillance screening during ICU admission, only 25 patients (0.22%) developed a clinically significant MRSA infection requiring treatment resulting in an NPV of 99.4% (95% confidence interval [CI] 99.1-99.6). The investigators estimated that 7364 days of vancomycin therapy could have been avoided if vancomycin had been discontinued in the patients with negative swab results.…”
Section: Nonspecific (Any Source) Infectionsmentioning
confidence: 99%